2009
DOI: 10.1163/156854109x428034
|View full text |Cite
|
Sign up to set email alerts
|

Pseudaphelenchus yukiae n. gen., n. sp. (Tylenchina: Aphelenchoididae) associated with Cylindrotermes macrognathus (Termitidae: Termitinae) in La Selva, Costa Rica

Abstract: A species of aphelenchoidid nematode was isolated from a subterranean termite, Cylindrotermes macrognathus, during a survey of termite-associated nematodes in a conserved forest in La Selva, Costa Rica. The nematode was morphologically intermediate between the families Aphelenchidae and Aphelenchoididae, i.e., the nematode had a true bursa supported by bursal limb-like genital papillae but lacked a clear pharyngeal isthmus. The molecular phylogenetic status of the new nematode among tylenchid, cephalobid, pana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The 19 tentatively recognized genera were separated into free-living fungal feeder ( Pseudaphelenchus ), entomopathogen ( Steinernema ), insect parasite (Tylenchid parasite) and free-living bacteria feeders ( Poikilolaimus , Rhabditis , Oscheius , Halicephalobus , Oigolaimella , Bunonema , Cruznema and Rhabd1) [22] , [23] . However, the feeding resources for the other eight genera, Aphel1-3, Diplo1-4 and Panagrolaimomorpha were not specified or clearly delineated because of low taxonomic resolution.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 19 tentatively recognized genera were separated into free-living fungal feeder ( Pseudaphelenchus ), entomopathogen ( Steinernema ), insect parasite (Tylenchid parasite) and free-living bacteria feeders ( Poikilolaimus , Rhabditis , Oscheius , Halicephalobus , Oigolaimella , Bunonema , Cruznema and Rhabd1) [22] , [23] . However, the feeding resources for the other eight genera, Aphel1-3, Diplo1-4 and Panagrolaimomorpha were not specified or clearly delineated because of low taxonomic resolution.…”
Section: Resultsmentioning
confidence: 99%
“…In the present and previous studies, we demonstrated that a MOTU/morphology survey (reverse taxonomy) followed by re-isolation and culturing attempts improved the efficiency of identification and led to the discovery of new species and genera to science and improved the resolution of the database for future work [21] , [22] , [39] . Thus, we consider that the reverse taxonomy method effectively works for the biodiversity survey of nematodes that are culturable, as well as other poorly studied microscopic organisms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations